Preoperative FIBTEM Predicts Postoperative Hemorrhage in Total Knee Arthroplasty - Kim, Seong-Hyop; Oh, Chung-Sik; Kim, Tae-Hoon; Park, Sewon; Rhee, Ka Young (The Journal of Knee Surgery, 2018)
FIBTEM parameters might predict the amount of postoperative hemorrhage following total knee arthroplasty (TKA), because fibrin polymerization and fibrinolysis have a central role in postoperative hemorrhage following TKA. This study retrospectively evaluated 54 patients who had undergone unilateral primary TKA. Laboratory coagulation parameters, including FIBTEM, were recorded before anesthesia induction and after admission to the postanesthetic care unit. The decrease in hemoglobin (Hb), amount of hemorrhage via closed suction drainage, fluid administration, and amount transfused were reviewed postoperatively. The preoperative FIBTEM amplitudes 10 (A10) and 20 (A20) minutes after clotting time and maximum clot firmness (MCF) had the highest correlations with the postoperative decrease in Hb (p = 0.001, p = 0.002, and p = 0.003, respectively). The preoperative FIBTEM A10 <19 mm, A20 <20 mm, and MCF < 21 mm predicted > 3.0 g/dL postoperative Hb decrement from the postanesthetic Hb value (p = 0.004, p = 0.007, and p = 0.012, respectively). Preoperative FIBTEM can predict the amount of postoperative hemorrhage following TKA.
Keywords: patient blood management; FIBTEM; total knee arthroplasty